Study of Hardening Process of AISI 1045 Steel Material with Variation of Heating Temperature, Media, and Cooling Media Volume for Shaft Application - Setiawan, Heri; Ruskandi, Cecep; Latif, Abdul (International Journal of Marine Engineering Innovation and Research, 2025)
Shafts are critical components in engines that facilitate power transmission and rotation. AISI 1045 steel is a cheap alternative for shaft manufacturing, but a proper selection of heat treatment parameters is required to optimize its mechanical properties. This research aims to study the process effect of heating temperature, type of cooling media, and volume ratio of cooling media on the hardness and wear of AISI 1045 material. The results show that the kind of cooling media significantly affects hardness and wear, while the heating temperature and cooling media volume ratio are not significant. The heat treatment process at 850°C with water cooling and a ratio of 12:1 resulted in a hardness of 60 HRC and a wear rate of 0.00335 grams. However, further studies on the tempering process and other parameter adjustments are required to achieve optimum performance.